An Analysis of Property Development Projects: HIGH HILLS Setiabudi & DERMA JAYA Samudera Jaya - Muktamar, Riri (The Indonesian Journal of Business Administration, 2013)
HIGH HILLS and DERMA JAYA as property developers need to relate the competitors’ project and condition of neighborhood (infrastructures and facilities), in determining market segmentation, and the way of to enhance their system by doing sort of analysis with several factors that shall be considered in conducting those analysis. This research combines the basic principles of project management, with strategic management and marketing management. It’s been conducted in a very simple way, but trustfully to be workable in property development sector. Even though there are numerous elements affecting a property development project, but this research will focus on the application of SWOT analysis in strategic management, 4Ps in marketing management and TQC in project management. Through process of observing neighborhood condition and analyzing competitor’s property development projects, author took a conclusion that mid-low customers are the most appropriate segment for DERMA JAYA’s project in Samudera Jaya, Bekasi Utara. Employees of a lot of industries in surrounding areas from supervisor to manager level are potential buyers for DERMA JAYA’s property products. Through process of observing neighborhood condition and analyzing competitor’s property development projects, author took a conclusion that mid-up to premium customers are the most appropriate segments for HIGH HILLS’ project in Sersan Bajuri, Bandung. Local people of Bandung and people from outside Bandung who have interest to own classy properties in North Bandung are very potential to be HIGH HILLS’ product buyers. In order to improve its system, DERMA JAYA and HIGH HILLS are recommended to create sort of standardized forms to control all steps of construction since the early constructing foundation to finishing process, in order to assure that all works are being done in accordance with company quality standards and government regulation. Another recommendation is to create a solid marketing team, in order to make sure that all products are feasibly marketed. Marketing team is to be actively involved in future development process. Their idea and opinion are to be taken as consideration in establishment of future marketing strategy. Keywords: SWOT Analysis, TQC Analysis, 4Ps Analysis.